2020
DOI: 10.1002/cpp.2531
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and healing in the underserved populations of homelessness and corrections: Forgiveness Therapy as an added component to intervention

Abstract: The purpose of this article is to begin applying the principles of the psychology of forgiveness to people who are without homes and people who are in prisons. A review of the literature shows trauma for both groups. When the trauma is caused by unjust treatment by others, then excessive anger can result, compromising one's psychological and physical health. We review the interventions that have been offered for those without homes and the imprisoned to examine which existing programmes address such anger. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 180 publications
(281 reference statements)
1
6
0
Order By: Relevance
“…Because forgiveness shows promise as an effective therapy to relieve psychological compromise (anger, anxiety and depression), and to restore psychological well‐being (hope, self‐esteem and empathy), perhaps Forgiveness Therapy may be a first step in effective rehabilitation within a correctional context, given the findings discussed above showing trauma in childhood and subsequent resentment by those who are incarcerated. To date, there are no randomized clinical trials centred on Forgiveness Therapy in a maximum‐security correctional institution (see the literature review, Song, Yu, & Enright, 2020). It may be time for such a study especially given a relatively recent call for such research that has yet to be carried out (Enright et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because forgiveness shows promise as an effective therapy to relieve psychological compromise (anger, anxiety and depression), and to restore psychological well‐being (hope, self‐esteem and empathy), perhaps Forgiveness Therapy may be a first step in effective rehabilitation within a correctional context, given the findings discussed above showing trauma in childhood and subsequent resentment by those who are incarcerated. To date, there are no randomized clinical trials centred on Forgiveness Therapy in a maximum‐security correctional institution (see the literature review, Song, Yu, & Enright, 2020). It may be time for such a study especially given a relatively recent call for such research that has yet to be carried out (Enright et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Criminological, psychological and educational theories and practices based on the ethics of care support the notion that the best practice for increasing human good and decreasing suffering is our human love and compassion (Baskin & Slaten, 2010; Enright et al, 2016; Gilligan, 1993; Kohen, 2009; Noddings, 1984; Ronel & Elisha, 2011; Shonin et al, 2013; Song et al, 2020). In criminology specifically, this notion is supported by models that promote caring norms such as positive criminology (Ronel & Elisha, 2011); positive victimology (Ronel, 2015); compassion therapy (Shonin et al, 2013; Song et al, 2020; Stefanakis, 2008); forgiveness and self-forgiveness therapy (Enright et al, 2016; Kohen, 2009); and GLM (McNeill, 2006; Ward & Maruna, 2007; Ward & Salmon, 2011). While criminal justice-oriented therapy usually works with people who offended through the threat-protection-focused and drive-focused systems, compassion-focused therapy aims at working through people’s affiliative soothing system, which is highly sensitive to interpersonal cues of social safeness, acceptance and care, and can regulate the two other systems.…”
Section: Principles Of Spiritual Companionship With People Who Offendedmentioning
confidence: 99%
“…Moreover, prisoners who were exposed to a victim awareness procedure were more aware of the harm caused to the victim and demonstrated more favorable attitudes toward participating in a restorative-justice process (Weimann-Saks & Peleg-Koriat, 2020). Thus, forgiveness of others predicted self-forgiveness (Krentzman et al, 2018) and self-forgiveness was found effective in leading prisoners to become better people (Song et al, 2020), and those who have experienced the emotional consequences of their deeds, which facilitated self-work toward responsibility-taking (Woodyatt et al, 2017).…”
Section: Spiritual Companionship With People Who Offendedmentioning
confidence: 99%
See 1 more Smart Citation
“…Forgiveness is an individual's decision to respond to others' behaviors that commit something unfair toward the current individual (Song et al, 2020). People that forgive verbal bullies can develop positive attitudes (Enright & Fitzgibbons, 2004;Hidayah et al, 2021).…”
Section: Cognitive Behavior Counseling For Forgivingmentioning
confidence: 99%